Pengaruh Menghafal Al-Qur’an terhadap Peningkatan Aspek Kognitif SMA Bustanul Ulum Jayasakti Anak Tuha Lampung Tengah - Maulidin, Syarif; Abdun Jamil, Muhammad (Al-Bustan: Jurnal Pendidikan Islam, 2024)
Memory ability plays an important role in achieving optimal results in cognitive aspects, especially in the context of education which is measured through learning achievement. One of the methods used to hone memory is through memorizing the Qur'an. A study was conducted to examine the effect of the ability to memorize the Qur'an on improving cognitive aspects in tahfidz class students at Bustanul Ulum High School in Central Lampung. The research method used was quantitative involving 33 participants. Data were collected through observation, questionnaires to assess the ability to memorize the Qur'an, and documentation of students' report cards. The results showed that the ability to memorize the Qur'an had a significant effect on improving students' cognitive aspects, with an R Square value of 29.7%. That is, about 29.7% of the improvement in cognitive aspects can be explained by the ability to memorize the Qur'an. Other factors outside the method of memorizing al-Qur'an also contribute to the increase.